VALUATION OF STOCKS LISTED ON IDX HIGH DIVIDEND 20 INDEX (2018-2020) USING DISCOUNTED CASH FLOW (DCF) MODEL - Xaviera, Athena; Wijayanti, Risna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research’s background was based on the increasing number of investors in Indonesia’s capital market – including stock investment – especially in 2020. With such growth and enthusiasm regarding stock investment, the stock valuation may take place so investors can attain benefits and avoid loss. IDX High Dividend 20 (IDXHIDIV20) has good performance, and investors actively trade its stocks in the market; hence, stock valuation was deemed necessary. Discounted Cash Flow (DCF) was used to determine whether stocks are undervalued, fair valued, or overvalued. The type of this research was descriptive with a quantitative approach. The sample used was stocks listed on the IDXHIDIV20 index from 2018-2020, comprised of 27 stocks. This research showed that most of the stocks were overvalued throughout 2018-2020, with a percentage of 63%, 56%, and 59%, respectively. Among 15 consistently listed on the IDXHIDIV20 index throughout 2018-2020, 11 stocks were overvalued, and four were undervalued. As for the 12 inconsistently listed stocks, five stocks were overvalued, and seven were undervalued. Investors may sell or avoid the purchase of overvalued stocks and instead buy undervalued ones.